2021
DOI: 10.1038/s41598-021-00235-4
|View full text |Cite
|
Sign up to set email alerts
|

The role of borosilicate glass in Miller–Urey experiment

Abstract: We have designed a set of experiments to test the role of borosilicate reactor on the yielding of the Miller–Urey type of experiment. Two experiments were performed in borosilicate flasks, two in a Teflon flask and the third couple in a Teflon flask with pieces of borosilicate submerged in the water. The experiments were performed in CH4, N2, and NH3 atmosphere either buffered at pH 8.7 with NH4Cl or unbuffered solutions at pH ca. 11, at room temperature. The Gas Chromatography-Mass Spectroscopy results show i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(31 citation statements)
references
References 47 publications
0
24
0
Order By: Relevance
“…After such a step, the gas was condensed into the first flask and cyclically subjected to the same process. A recent reproduction of the Miller–Urey experiments, highlighting the (previously overlooked) role played by the borosilicate glasses composing the surfaces of the flasks, was conducted by Saladino, Di Mauro, and coworkers [ 78 ].…”
Section: Results and Discussionmentioning
confidence: 99%
“…After such a step, the gas was condensed into the first flask and cyclically subjected to the same process. A recent reproduction of the Miller–Urey experiments, highlighting the (previously overlooked) role played by the borosilicate glasses composing the surfaces of the flasks, was conducted by Saladino, Di Mauro, and coworkers [ 78 ].…”
Section: Results and Discussionmentioning
confidence: 99%
“…121,122 Criado-Reyes et al have followed up on the experiment and found that borosilicate glass plays a decisive role for the outcome. 123 By comparing the reaction in Teflon® vessels and in Teflon® vessels containing small pieces of borosilicate glass to the original experiment carried out in a borosilicate vessel, they were able to demonstrate that the presence of glass clearly affected the reaction. In the presence of borosilicate glass, a dipeptide, dicarboxylic acids, polycyclic aromatic compounds and several biological nucleobases were formed exclusively, or to a greater extent, compared to the reaction in a Teflon® vessel.…”
Section: Glass Surface As a Heterogeneous Brønsted Base-catalystmentioning
confidence: 96%
“…1. If the formula is a fuzzy formula instead of a discrete formula, replace the -f flag with a -fuzzy flag, and enclose any element intervals in brackets (e.g., use C [5][6][7]H [12][13][14][15] to ensure that all structures generated have between 5 and 7 carbon atoms and between 12 and 15 hydrogen atoms).…”
Section: Java -Jar [Maygen Jar File Name] -F [Chemical Formula]v -O [...mentioning
confidence: 99%